Rapid diagnostic test for antenatal syphilis screening in low-income and middle-income countries: a systematic review and meta-analysis. Issue 2 (21st February 2018) - Phang Romero Casas, Carmen; Martyn-St James, Marrissa; Hamilton, Jean; Marinho, Daniel S; Castro, Rodolfo; Harnan, Sue
Abstract : Objectives: To undertake a systematic review and meta-analysis to evaluate the test performance including sensitivity and specificity of rapid immunochromatographic syphilis (ICS) point-of-care (POC) tests at antenatal clinics compared with reference standard tests (non-treponemal (TP) and TP tests) for active syphilis in pregnant women. Methods: Five electronic databases were searched (PubMed, EMBASE, CRD, Cochrane Library and LILACS) to March 2016 for diagnostic accuracy studies of ICS test and standard reference tests for syphilis in pregnant women. Methodological quality was assessed using QUADAS-2 (Quality Assessment of Diagnostic Accuracy Studies). A bivariate meta-analysis was undertaken to generate pooled estimates of diagnostic parameters. Results were presented using a coupled forest plot of sensitivity and specificity and a scatter plot. Results: The methodological quality of the five included studies with regards to risk of bias and applicability concern judgements was either low or unclear. One study was judged as high risk of bias for patient selection due to exclusion of pregnant women with a previous history of syphilis, and one study was judged at high risk of bias for study flow and timing as not all patients were included in the analysis. Five studies contributed to the meta-analysis, providing a pooled sensitivity and specificity for ICS of 0.85 (95% CrI: 0.73 to 0.92) and 0.98 (95% CrI: 0.95 to 0.99), respectively. Conclusions: This review and meta-analysis observed that rapid ICS POC tests have a high sensitivity and specificity when performed in pregnant women at antenatal clinics. However, the methodological quality of the existing evidence base should be taken into consideration when interpreting these results. PROSPERO registration number: CRD42016036335 .